The Impact of Female Students' Breast Self-Examination training on their Mothers' Awareness - Elieh Abasi; Homaira Tahmasebi; Mandana Zafari; Maryam Tofigi; Sogra Hassani (Mashhad University of Medical Sciences, 2018)
Background & aim: Breast cancer is the most common cancer in women, which its early diagnosis is of paramount importance for the prevention of its associated mortality and morbidity. Breast self-examination (BSE) is one of the methods for the early detection of breast cancer. Education plays an important role in increasing BSE practice. Regarding this, the present study was conducted to measure the impact of BSE training to female students on their mothers' awareness. Methods: This quasi-experimental study was conducted on 100 university students and their mothers in Sari, Iran, in 2015. After educating the students about BSE, they were asked to train their mothers in this regard. The data were collected before and one month after training, using demographic, BSE attitude assessment, and BSE questionnaires. Data analysis was performed in SPSS software (version 17) using descriptive statistics, Chi-square test, t-test, and Fisher's exact test. Results: The results of the independent t-test revealed a significant difference between the two groups in terms of knowledge at the post-training stage (P=0.000). Furthermore, the two groups had significant mean differences in the knowledge scores obtained before and after the training (P